1988
DOI: 10.1111/j.1398-9995.1988.tb00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with partially purified and standardized tree pollen extracts

Abstract: Patients allergic to pollen from alder, birch and hazel were hyposensitized during a 3-year period with either birch pollen extract alone (n = 24) or a mixture of one or more of alder, birch and hazel pollen extracts (n = 27). The effect of the treatment was evaluated by RAST and tandem crossed-radioimmunoelectrophoresis (tandem-CRIE). The patient' specific IgE response to the major allergens of alder (Aln g I), birch (Bet v I) and hazel (Cor a I and Cor a II), as measured by tandem-CRIE, and the total specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It has been shown that immunotherapy with birch pollen extract and recombinant birch pollen allergen, Bet v 1 and rBet v 1 derivatives induces protective IgG responses against the cross-reactive Fagales pollen and plant food allergens and may improve allergic symptoms to the birch-pollen-related allergen sources [6,7,8, 14,29,30,31]. In particular, injection immunotherapy trials with adjuvant-bound purified recombinant birch pollen allergen Bet v 1 and with genetically modified derivatives of Bet v 1 have demonstrated that treatment with purified Bet v 1 induces highly specific, robust and protective IgG responses not only to natural Bet v 1 [32], but also to Bet v 1-cross-reactive plant allergens [14, 31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that immunotherapy with birch pollen extract and recombinant birch pollen allergen, Bet v 1 and rBet v 1 derivatives induces protective IgG responses against the cross-reactive Fagales pollen and plant food allergens and may improve allergic symptoms to the birch-pollen-related allergen sources [6,7,8, 14,29,30,31]. In particular, injection immunotherapy trials with adjuvant-bound purified recombinant birch pollen allergen Bet v 1 and with genetically modified derivatives of Bet v 1 have demonstrated that treatment with purified Bet v 1 induces highly specific, robust and protective IgG responses not only to natural Bet v 1 [32], but also to Bet v 1-cross-reactive plant allergens [14, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Both forms of therapy were shown to be equally effective in an extensive analysis published in 1988 [6,7,8]. However, a study published 2 years earlier had indicated that a mixture of birch-alder-hazel pollen seemed to be more effective in reducing symptoms than birch pollen extract alone [9].…”
Section: Introductionmentioning
confidence: 99%
“…Second, rBet v 1 was found to inhibit the majority of IgE reactivity to pollen allergens from trees of the order Fagales (alder, hazel, hornbeam) and plant-derived food in patients with birch pollen-related oral allergy syndrome [47, 118]. Third, it has been shown that immunotherapy with birch pollen extract was effective in treating allergies not only to birch, but also to pollens of trees of the Fagales order and to birch-related plant foods [154,155,156,157]. Fourth, it has been demonstrated that patients who reacted exclusively with Bet v 1 had a better clinical outcome when treated with birch pollen extract than patients reacting also with other allergens [158].…”
Section: Rbet V 1 As a Diagnostic Marker Allergen To Identify Genuinementioning
confidence: 99%
“…Since Bet v 1 and Bet v 2 bind more tree pollen–specific IgE than any other pollen allergen from hazel, oak, birch, alder or hornbeam, they appear to be the most allergenic pollen proteins from these trees. Together, these two allergens harbor most of the IgE epitopes of the Fagales pollen allergens [52], indicating that these birch pollen allergens alone may be effective in diagnosing and treating Fagales pollen allergen [53, 54, 55]. Bet v 3 and Bet v 4 have been identified as calcium–binding proteins [56, 57].…”
Section: Non–anaphylactic Forms Of the Major Birch Pollen Allergen Bmentioning
confidence: 99%